Competency Improvement Through Character Education and Utilization of Digital Technology for SMA and SMK in Bandung and Tasikmalaya (Studies at Islamic Boarding School Ulul Albab Bandung and SMAN 2 Tasikmalaya) - Btari Mariska Purwaamijaya; Adi Prehanto; Yogi Prasetyo; Alifia Fatimatun Nazya (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
In the Industrial Revolution 4. 0, the integration of automation and artificial intelligence has led to significant changes in various sectors, offering the potential for promising advances in efficiency and develop. Research on perception and prospective analysis of artificial intelligence and its impact on human resources in Indonesia's industry 4.0 highlights the central role of human resources (HR) in the adaptation process of Indonesia in today's industrial era. Even as artificial intelligence brings about significant technological advances, the fundamental role of human values ​​promoted by HR remains an important factor in this transformation. Faced with this challenge, the role of teachers in higher education environments becomes important as change agents capable of integrating theoretical knowledge with real-world practical experiences. To cope with these changes, specific training courses have been designed to enhance the skills of students and teachers, especially in the areas of character building and the use of digital technology.  This training includes the use of social media and multimedia as educational tools, as well as applying the three dharma principles of higher education through community service activities. Through this effort, we hope universities can play an active role in preparing human resources capable of adapting and responding to global changes while preserving the values and importance of people in the era of Industry 4.0.